Cytokines at the Interplay Between Asthma and Atherosclerosis? - Gurgone, Danila; McShane, Lucy; McSharry, Charles; Guzik, Tomasz J.; Maffia, Pasquale (Frontiers in Pharmacology, 2020)
Cardiovascular disease (CVD) is an important comorbidity in a number of chronic inflammatory diseases. However, evidence in highly prevalent respiratory disease such as asthma are still limited. Epidemiological and clinical data are not univocal in supporting the hypothesis that asthma and CVD are linked and the mechanisms of this relationship remain poorly defined. In this review, we explore the relationship between asthma and cardiovascular disease, with a specific focus on cytokine contribution to vascular dysfunction and atherosclerosis. This is important in the context of recent evidence linking broad inflammatory signalling to cardiovascular events. However inflammatory regulation in asthma is different to the one typically observed in atherosclerosis. We focus on the contribution of cytokine networks encompassing IL-4, IL-6, IL-9, IL-17A, IL-33 but also IFN- and TNF-α to vascular dysfunction in atherosclerosis. In doing so we highlight areas of unmet need and possible therapeutic implications.